2021
DOI: 10.1371/journal.pgen.1009364
|View full text |Cite
|
Sign up to set email alerts
|

A complex genetic architecture in zebrafish relatives Danio quagga and D. kyathit underlies development of stripes and spots

Abstract: Vertebrate pigmentation is a fundamentally important, multifaceted phenotype. Zebrafish, Danio rerio, has been a valuable model for understanding genetics and development of pigment pattern formation due to its genetic and experimental tractability, advantages that are shared across several Danio species having a striking array of pigment patterns. Here, we use the sister species D. quagga and D. kyathit, with stripes and spots, respectively, to understand how natural genetic variation impacts phenotypes at ce… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 99 publications
0
14
0
Order By: Relevance
“…Quantitative descriptors of phenotypes and phenotypic variation are, therefore, critical for analyzing development, population variability and evolutionary diversification. Prior analyses of Danio pigmentation have relied principally on quantifications of cell numbers and positions relative to body axes, as well as nearest neighbor distances and binarized melanophore pattern elements ( McCluskey et al, 2021 ; Mills et al, 2007 ; Parichy and Turner, 2003a ; Patterson et al, 2014 ; Quigley et al, 2005 ; Spiewak et al, 2018 ). Because no single descriptor can fully characterize the complexity and variety of the patterns across Danio species and zebrafish mutants, we sought new metrics to facilitate mechanistic analyses and to enable a deeper understanding of pattern diversification, and particularly the morphospace within which development occurs ( Raup, 1961 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantitative descriptors of phenotypes and phenotypic variation are, therefore, critical for analyzing development, population variability and evolutionary diversification. Prior analyses of Danio pigmentation have relied principally on quantifications of cell numbers and positions relative to body axes, as well as nearest neighbor distances and binarized melanophore pattern elements ( McCluskey et al, 2021 ; Mills et al, 2007 ; Parichy and Turner, 2003a ; Patterson et al, 2014 ; Quigley et al, 2005 ; Spiewak et al, 2018 ). Because no single descriptor can fully characterize the complexity and variety of the patterns across Danio species and zebrafish mutants, we sought new metrics to facilitate mechanistic analyses and to enable a deeper understanding of pattern diversification, and particularly the morphospace within which development occurs ( Raup, 1961 ).…”
Section: Resultsmentioning
confidence: 99%
“…Danio pigment patterns offer an outstanding opportunity to learn about the genetic and cellular mechanisms underlying trait evolution, given their largely two-dimensional organization, tractable number of cell types, accessibility to imaging as phenotypes are developing, and approaches available for interrogating developmental genetic mechanisms and modeling pigment cell behaviors ( McCluskey et al, 2021 ; Moreira and Deutsch, 2005 ; Nakamasu et al, 2009 ; Owen et al, 2020 ; Patterson et al, 2014 ; Patterson and Parichy, 2019 ; Podobnik et al, 2020 ; Spiewak et al, 2018 ; Volkening and Sandstede, 2015 , 2018 ; Watanabe and Kondo, 2015b ; Yamanaka and Kondo, 2014 ). Given their developmental origins, these patterns may inform our understanding of species differences in other neural crest derived traits as well.…”
Section: Introductionmentioning
confidence: 99%
“…Danio albolineatus were derived from individuals collected in Thailand by M. McClure in 1995 ( McClure et al, 2006 ), provided to the laboratory of S. Johnson, and then maintained in our laboratory from 2000 until the present. Additional species of Danio used for assessing erythrophore complements were obtained directly from the field or through the pet trade [ D. aesculapii; D. quagga , D. kyathit ( McCluskey et al, 2021 ) D. nigrofasciatus , D. tinwini ( Spiewak et al, 2018 ); D. kerri; D. choprae; D. margaritatus , D. eythromicron ] and maintained subsequently in the lab or were observed in the field [ D. meghalayensis , D. dangila ( Engeszer et al, 2007 )]. Fish were reared under standard conditions to maintain D. rerio (~28 °C; 14 L:10D) with larvae fed initially marine rotifers, derived from high-density cultures and enriched with Rotimac and Algamac (Reed Mariculture), with older larvae and adults subsequently fed live brine shrimp and a blend of flake foods enriched with dried spirulina.…”
Section: Methodsmentioning
confidence: 99%
“… ( A ) Examples of major carotenoid types including yellow zeaxanthin, red astaxanthin, and orange β-carotene, with factors required for entry into cells and chemical modification (Main text). ( B ) Erythrophore presence (red circles) or absence (light gray circles) indicated by direct observation or prior species descriptions ( Fang and Kottelat, 2000 ; Quigley et al, 2005 ; Engeszer et al, 2007 ; Kullander and Fang, 2009 ; Kullander, 2012 ; Kullander and Norén, 2016 ; Spiewak et al, 2018 ; McCluskey et al, 2021 ). A composite phylogeny based on several molecular evolutionary studies is shown; gray branches indicate lineage placements inferred by morphology alone ( Tang et al, 2010 ; Kullander, 2012 ; Kullander et al, 2015 ; McCluskey and Postlethwait, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Examples of major carotenoid types including yellow zeaxanthin, red astaxanthin, and orange β-carotene, with factors required for entry into cells and chemical modification (Main text). (B) Erythrophore presence (red circles) or absence (light grey circles) indicated by direct observation or prior species descriptions (Spiewak et al;Fang and Kottelat, 2000;Quigley et al, 2005;Engeszer et al, 2007;Kullander and Fang, 2009;Kullander, 2012;Kullander and Noren, 2016;McCluskey et al, 2021). A composite phylogeny based on several molecular evolutionary studies is shown; grey branches indicate lineage placements inferred by morphology alone (Tang et al, 2010;Kullander, 2012;Kullander et al, 2015;McCluskey and Postlethwait, 2015).…”
Section: Statistical Analysesmentioning
confidence: 99%